Optimization of Learning The Quran and Hadith Through the Jazariyah Book to Improve Students' Quran Reading Ability - Suryanto, Andika; Amirudin, Amirudin; Yusuf, Muhammad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to 1) How is the Optimization of Al-Qur'an Hadith Learning Through the Jazariyah Book to Improve the Ability to Read the Qur'an of Students (Case Study at the An-Nahdliyah Tri Bhakti At-Taqwa Islamic Boarding School, Class 2 Wustho Putra) Rama Puja Raman Utara East Lampung in 2024? 2) What are the factors that influence the Optimization of Al-Qur'an Hadith Learning Through the Jazariyah Book to Improve the Ability to Read the Al-Qur'an of Students (Case Study at Madrasah Dinniyah An-Nahdliyah Tri Bhakti At-Taqwa Class 2 Wustho Putra) Rama Puja Raman Utara East Lampung in 2024. The purpose of this study is to identify how to optimize the use of the Jazariyah book in learning the Al-Qur'an at Madrasah Dinniyah An-Nahdliyah Tri Bhakti At-Taqwa class 2 Wustho Putra to improve the ability to read the Al-Qur'an of students. This study uses a qualitative approach using field research. Data collection techniques are through observation, documentation, and interviews. Data analysis techniques and data validity use deductive techniques, source triangulation and techniques to ensure the reliability of the data obtained and prevent subjectivity on the part of the researcher. In addition, researchers cross-check with various sources to observe data and make observations more than once. And in essence data analysis is grouping variable data and types of respondents to answer the problem formulation. The results of this study are 1)Al-Jazariyah Book as a Structured Tajweed Guide. 2) Al-Jazariyah Book offers a very structured explanation of the rules of tajweed that must be applied in reading the Qur'an. Improving the Ability to Read the Qur'an Correctly. 3). Through this learning, students will not only master the rules of tajweed, but also understand the beauty of reading the Qur'an and how to apply it in everyday life.